Kooperative Raumplanung Handlungsformen und Verfahren - Hoffmann, Kristin (sui generis Verlag, 2021)
Cooperative planning is a potent approach for steering quality settlement development inwards. With the combination of (special) use plans and urban development contracts, they come into play where traditional spatial planning is unable to reliably achieve the desired spatial planning due to a lack of agreements with landowners or investors. While private individuals benefit from a better use of their land, the state gains influence on the "if" and "how" of the constructional realization of this land. The considerable urban planning significance of cooperative planning is contrasted by constitutional concerns about the method. Cooperative planning runs the risk of shortchanging legitimate public and third-party interests and of overreaching to the private cooperating party because of the state's bidding power in the area of land use planning. This book shows ways how cooperative planning can be designed according to rule-of-law standards and thus be strengthened.